A Facile Approach to Efficiently Load and Isolate CoN Active Sites for the Preparation of a High‐Performance Co–N–C Oxygen Reduction Catalyst. Issue 4 (17th February 2023) - Jiang, Binghan; Liu, Xue; Wang, Fuling; Ren, Jianwei; Yang, Tianle; Jin, Zhicheng; Li, Xiyou; Chen, Yanli
Abstract : A facile approach is developed for the preparation of an oxygen reduction reaction (ORR) catalyst Co–N–GA‐1 by pyrolyzing a well‐designed precursor CoTPP/H2 TPP@OGA. In the precursor, Co is preanchored into the porphyrinato cobalt CoTPP molecule by Co‐N4 core that is further protected by the metal‐free porphyrin H2 TPP depending on the intermolecular π–π interaction during the self‐assembled process on the surface of lipophilic porous original graphene aerogel. The resulted Co–N–GA‐1 owns a Co elemental content up to 1.67%, which is ≈13 times than that of Co‐N‐CB‐1 originated from a CoTPP/H2 TPP precursor absorbed on commercial carbon black. Meanwhile, CoN content accounts for 71.7% of the total Co‐based species in the Co–N–GA‐1, more than that of CoN‐GA‐2 (58.9%) originated from the CoTPP@OGA precursor. Consequently, Co–N–GA‐1 exhibits the most ORR performance among the present three catalysts with the more positive onset and half‐wave potentials of 0.96 and 0.88 V vs reversible hydrogen electrode, respectively, also superior to those of the commercial 20 wt% Pt/C and most of the Co‐based catalysts reported so far. Furthermore, Zn‐air battery assembled with Co–N–GA‐1 exhibits a higher peak power density of 110 mW cm −2 and excellent durability than that with Pt/C. Abstract : CoTPP/H2 TPP is deposited in situ on the original graphene aerogel through a self‐assembled process. The highly adsorptive and lipophilic characteristics ensure graphene aerogels as an effective carrier to load active sites, in which the Co central metal in CoTPP is further protected by π–π interaction between CoTPP and H2 TPP. Co–N–GA‐1 exhibits excellent oxygen reduction reaction activity as a Co‐based electrocatalyst.